Analisis Motor Ability Terhadap Keterampilan Teknik Permainan Futsal pada Anak Usia 11 Tahun - Habibi Sutirta; Abdurrauf Abdul Karim (Gladi : Jurnal Ilmu Keolahragaan, 2020)
The research is correlational and inferential, so it is necessary to design and examine the contribution of strength, speed, agility, and explosive power toward technical skill in futsal. The results of the research reveal that (1) there is significant contribution of strength towards students' Technical Skillin futsal at SD Rama Sejahtera Kecamatan Panakukang Kota Makassar by 50,8% proved from the result of analysis which obtained observation regression value (Ro) = 28,903 (p<0,05) with determination coeffiecient by 0,508. (2) there is significant contribution of speed towards students' technical skill in futsal at SD Rama Sejahtera Kecamatan Panakukang Kota Makassar by 38,8% proved from the result of analysis which obtained observation regression value (Ro) = 17,730 (p<0,05) with determination coeffiecient by 0,388. (3) there is significant contribution of agility towards students' technical skill in futsal at SD Rama Sejahtera Kecamatan Panakukang Kota Makassar by 28,0% proved from the result of analysis which obtained observation regression value (Ro) = 10,914 (p<0,05) with determination coeffiecient by 0,280. (4) there is significant contribution of explosive power towards students' technical skill in futsal at SD Rama Sejahtera Kecamatan Panakukang Kota Makassar by 62,3% proved from the result of analysis which obtained observation regression value (Ro) = 46,194 (p<0,05) with determination coeffiecient by 0,623. (5) there are strength, speed, agility, and explosive power contribution towards students' technical skill in futsal at SD Rama Sejahtera Kecamatan Panakukang Kota Makassar by 66,9% proved from the result of analysis which obtained observation regression value (Ro) = 12,619 (p<0,05) with determination coeffiecient by 0,699.